Analysis of Improving Lecturer Performance Through Strengthening Visionary Leadership and Learning Organization in Indonesian Higher Education - Astaryadi, Eka Soni; Retnowati, Rita; Suhendra, Suhendra (Peneliti.net, 2023)
This study aims to analyze the improvement of lecturer performance through visionary leadership and strengthening the learning organization. The research employs a quantitative method with a survey approach. The sample consists of 172 lecturers selected using proportional random sampling techniques. Data collection involves a validated and reliable questionnaire. Data analysis techniques are used to describe the data, test prerequisites (normality, homogeneity, and linearity), and hypothesis testing using t-tests and coefficient of determination tests. The results of the study indicate: (1) there is a direct influence of visionary leadership on lecturer performance, falling into the strong category; and (2) there is a direct influence of the learning organization on lecturer performance, also falling into the strong category. The conclusion of this research is that lecturer performance can be improved through the development of visionary leadership and a learning organization.